The Bigfoot filmography fictional and documentary appearances in film and television - Coleman, David (McFarland, 2012)
"This work is a look at the cinematic history of Sasquatch, from the earliest trick films of Georges Méliès to the most up-to-date CGI efforts. Critical insights regarding the genre's development are offered, along with a filmography that includes every known film or television appearance of Sasquatch, Bigfoot and Yeti in both fictitious and documentary formats"--Provided by publisher.